Liver and spleen stiffness on ultrasound elastography are predictors of the occurrence of esophagogastric varices after balloon‐occluded retrograde transvenous obliteration. (29th March 2022) - Furuichi, Yoshihiro; Abe, Masakazu; Yoshimasu, Yuu; Takeuchi, Hirohito; Itoi, Takao
Abstract: Background: Balloon‐occluded retrograde transvenous obliteration (BRTO) is an effective treatment for gastric varices, but predictors associated with overall survival rate (OS) and occurrence of esophagogastric varices (EGV) have not yet been clarified. In this study, we clarified these predictors by performing ultrasound elastography and blood tests at various time points. Methods: A total of 34 patients were enrolled. The primary endpoint was to identify predictors associated with OS and EGV occurrence by univariate and multivariate analyses. Secondary endpoints were to extract the cut‐off values for OS and EGV occurrence, and to clarify chronological changes in liver stiffness (LS), spleen stiffness (SS), spleen index (SI), and portal vein flow volume (PVF). Time points were set as before BRTO (Bf), and 1 day (D1), 7 days (D7), 1 month (1M), 3 months (3M), and 6 months (6M) after BRTO. Results: Albumin‐bilirubin score Bf, fibrin‐4 index change 6M, and branched chain amino acids tyrosine molar ratio (BTR) 1M were predictors of OS on univariate analysis ( P = .021, .033, and .019, respectively) but were not extracted by multivariate analysis. The factors of LS 6M > 19.9 kPa and SS D7 > 21.7 kPa were predictors of the occurrence of EGV on multivariate analysis ( P = .029 and .025, respectively). PVF significantly increased with time after BRTO. Conclusion: Albumin‐bilirubin score and BTR had the possibility to associate with OS, and the predictors of reduced occurrence of EGV were LS < 19.9 and SS < 21.7. Abstract : Highlight Furuichi and colleagues clarified the predictors associated with esophagogastric varices after balloon‐occluded retrograde transvenous obliteration by performing ultrasound elastography and blood tests at various time points. Liver stiffness at 6 months > 19.9 kPa, spleen stiffness at day 7 > 21.7 kPa, and spleen index were predictors on multivariate analysis.